Conversion of Residual Oat Husk and Pine Sawdust by Co-Hydrothermal Carbonization Towards Biofuel Production for Pellet Stoves - Santander-Moya, R; Cubillos-Montecino, F; Diaz-Robles, L; Murillo-Romero, H (Elsevier B.V., 2021)
Due to the impact of household wood-burning on air quality and the controversy related to its carbon neutrality, the development of cleaner technologies is highly required. Valorization of agro-waste emerges as a potential strategy to cover the demand for wood-based fuels partially. Oat husk (OH) is a widely available waste, and its combination with pine sawdust (PS) can be a suitable alternative towards biofuel production. In this work, the conversion of OH-PS mixtures via hydrothermal carbonization (HTC) was investigated. Optimization of HTC process parameters in terms of mixing ratio (21.7–78.3% of OH loading) and reaction temperature (164.6–235.4 °C) was performed using the response surface methodology to maximize hydrochar yield (HY) and higher heating value (HHV) and to minimize ash content (AC). The optimal hydrochar was obtained at 21.7% OH and 228.3 °C after the responses were simultaneously optimized. Remarkably, the application of the optimized hydrochar was evaluated by combustion tests using a domestic pellet stove. Results revealed decreased emissions from incomplete combustion such as CO and particulate matter, far lower than local and global requirements. Besides, hydrochar pellets also exhibited decreased moisture uptake and enhanced durability, facilitating transportation and storage, especially when facing adverse conditions. These findings demonstrate the valorization of residual biomass via HTC is a viable approach to tackle the air pollution control associated with residential heating. © 2021 Elsevier B.V.